A STUDY ON STANDARDIZATION AND ASSESSMENT OF SENSORY AND MICROBIOLOGICAL QUALITY OF HERBAL RASAM - S, Vijayalakshmi; A, Arun; Arun, Kanchana (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Herbs have gained a widespread acceptance as a dietary constituent in Tamil Nadu, generally forming a substantial portion of the dietwhich serves as a therapeutic function. This study was aimed to formulate and standardize the four types of Rasam using four different herbs and toanalyze its quality changes in fresh Rasam and refrigerated Rasam (4Â±1Â°C). Appearance and odor scores of Rasam were satisfactory throughout thestorage. Sensory attributes were rated better for fresh Rasam than refrigerated Rasam, but all the attributes were decreased with increasing storageperiod. Methods: Microbiological quality of four types of different herbal Rasam was examined with freshly prepared Rasam and with refrigerated Rasam forthe presence of Escherichia coli, Staphylococcus aureus, Salmonella and Yeast, and Mold. Result: Comparison with the microbiological results shows in refrigerated Rasam-PAR, SAR, and AIR were at an acceptable level of microbiologicalquality whereas, Rasam-STR were at an unacceptable level of microbial quality due high level of total plate count and yeast and mold growth.Salmonella was examined, but it was not detected in all the four Rasam. Similarly, the microbial quality of all four freshly prepared Rasam showedhighly acceptable. Conductivity was measured for the presence of ions in solution. Conclusion: This study proposes that to minimize bacterial level in foods and always to consume freshly prepared Rasam than refrigerated. It alsoconcludes that good hygiene practices are necessary though the food serves a therapeutic function.